1951
DOI: 10.1111/j.1469-1809.1951.tb02484.x
|View full text |Cite
|
Sign up to set email alerts
|

Body Weight at Different Ages and Heights

Abstract: The articles published by the Annals of Eugenics (1925–1954) have been made available online as an historical archive intended for scholarly use. The work of eugenicists was often pervaded by prejudice against racial, ethnic and disabled groups. The online publication of this material for scholarly research purposes is not an endorsement of those views nor a promotion of eugenics in any way.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

1976
1976
2000
2000

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(35 citation statements)
references
References 12 publications
0
35
0
Order By: Relevance
“…Fifty-eight per cent of all the 60 patients to whom we gave Metformin were more then 20% over standard body weight (based on Kemsley's tables) [7], and had not satisfactorily responded to a standard diet of 1000 or 1400 calories alone. By "satisfactory" we mean fasting blood glucose levels below 100 mg/dl, and all 2 hour post-prandial levels below 140 mg/dl.…”
Section: Methodsmentioning
confidence: 98%
“…Fifty-eight per cent of all the 60 patients to whom we gave Metformin were more then 20% over standard body weight (based on Kemsley's tables) [7], and had not satisfactorily responded to a standard diet of 1000 or 1400 calories alone. By "satisfactory" we mean fasting blood glucose levels below 100 mg/dl, and all 2 hour post-prandial levels below 140 mg/dl.…”
Section: Methodsmentioning
confidence: 98%
“…No patient was uraemic and no patient was excluded because of the results of these investigations. Means+SD a Ideal body weight calculated from the data of Kemsley [5] Of the 65 patients treated by diet and oral therapy 22 were taking biguanides (mainly metformin), 21 patients sulphonylureas (mainly chlorpropamide) and 22 patients both sulphonylurea and biguanide therapy.…”
Section: Methodsmentioning
confidence: 99%
“…As early as 1952, Kemsley compared average weights in the United States, Britain and Japan, showing that at the same height and age, Britons and Japanese tend to be lighter than Americans. 2 More recently, Yanai et al reported that the prevalence of obesity in Japanese young populations needed to be estimated using ethnicspeci®c body mass index (BMI) values, rather than using those drawn from Caucasians, who tend to have a higher BMI in each age group. 3 In Brazil, local 17-y-old boys were found to be up to 10 kg leaner, compared with their peers in the US.…”
Section: Introductionmentioning
confidence: 99%